Development of Arduino-Yun-based JavaScript Logic Expression Programmable IoT for Automation System - Pratikto, .; Fitriani, Raydha Zul; Kuan, Yean-Der (Sensors and materials, 2020)
In this paper, a web-based application user interface (UI) to control Arduino input/output (I/O) through Hypertext Markup Language (HTML) and JavaScript logic expressions is developed. A simple server can be accessed from the internet and run on Arduino to support communication in controlling I/O, and is easier to operate as an IoT device. Arduino Yun is an option if the HTML file is sufficiently large because it is equipped with double processors and an SD card slot. Some scripts, namely, combination of OR and AND (ORN) direct on line (DOL), equivalent to start/stop or set/reset logic, as well as comparator, timer, and counter functions in one program line, are defined and then the command is equivalent to a programmable logic controller (PLC) ladder diagram rung. Arduino Yun is tested as a logic controller and applied to a virtual plant built using LabVIEW. The communication between the virtual plant in LabVIEW and Arduino Yun uses a NI DAQ 6009 USB device. The implementation results show that the input signal after undergoing one loop to give a signal to the virtual plant experiences a delay of 0.3 s, and this delay also occurs with the timer. If analog signals are included, the delay is 0.53 s.